Ultrasonography of the mammary gland and teat in cattle: A review - Tóth, Tamás; Kocsis, Róbert; Pajor, Ferenc; Póti, Péter; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
The authors summarized the knowledge of the literature about the ultrasonography of the udder and teat of the cattle. They describes the methodes of the ultrasoud examination. They discusses about what kind of parameters were examined in the healty cows. And what kind of abnormal lesions were diagnosed by ultrasound.
Keywords: cattle; ultrasound; udder; teat